Good Will Hunting - Van Sant, Gus; Williams, Robin, 1951-2014; Damon, Matt; Affleck, Ben, 1972-; Skarsgr̄d, Stellan; Driver, Minnie (Miramax collector's series., 1998)
A young working-class genius is hauled back from the brink of self-destruction by a gifted counselor.